Comparison of Lipid Profile in Insulin Dependent Diabetic Patients and Control Groups - Yasmeen Akhtar, Tabinda Ijaz, Fayyaz Ahmad, Muhammad Atif, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Insulin dependent diabetes mellitus is a worldwide health problem. In diabetic patients’ high levels of cholesterol leads to atherosclerosis and coronary heart diseases. Aim and Objective: Our objective was to investigate the comparison of dyslipidemia in insulin dependent diabetic patients and control group. Methods: A cross sectional study was done on 48 people in which 24 were insulin dependent diabetic patients and 24 were normal people, sample were taken from Gulab Devi hospital, Lahore. Blood samples were collected from both the patients and the control group after an overnight fasting for lipid profile and serum was separated from the whole blood by centrifugation. Samples were analyzed and the data was entered and analyzed by using SPSS version 20. Results: In this study increased triglycerides levels 21(87.5%), cholesterol levels 10(41.66%), LDL levels 8(33%), VLDL 21(87.5%) levels and decreased HDL levels 6(25%) were found in insulin dependent diabetic patients. Conclusion: We concluded that the levels of Cholesterol, Triglyceride, LDL and VLDL were increased in insulin dependent diabetic patients while HDL levels were low. Keywords: Lipid profile, Insulin dependent diabetes.